Emerging Paradigms in Sepsis Management: Critical Insights from Contemporary Clinical Trials - Sasidharan, Shibu; Dhillon, Harpreet (APIK Journal of Internal Medicine, 2025)
Sepsis remains a leading cause of mortality worldwide, despite advances in critical care medicine. This narrative review examines recent randomized controlled trials (RCTs) that have refined our understanding and management approaches to this complex syndrome. We conducted a comprehensive literature review of RCTs published over the last decade, focusing on sepsis management. Studies were selected based on methodological quality, sample size, and clinical relevance. Key domains included early recognition, fluid resuscitation, antimicrobial therapy, hemodynamic support, corticosteroid use, immunomodulation, artificial intelligence (AI) applications, and postsepsis care. Recent evidence supports the implementation of electronic early warning systems to facilitate timely interventions, the adoption of more restrictive fluid strategies with equivalent safety profiles between crystalloid solutions, utilization of rapid diagnostics and biomarkers for targeted antimicrobial therapy, optimization of hemodynamic support with consideration of novel vasopressors and perfusion targets, the judicious use of corticosteroids in select patients with septic shock, continued investigation of immunomodulatory therapies, the application of AI for phenotype identification and decision support, and structured postsepsis rehabilitation programs to improve long-term outcomes. While significant progress has been made in sepsis management, substantial challenges remain. Future research should focus on precision medicine approaches, novel therapeutic targets, and implementation strategies for resource-limited settings. The integration of clinical trials with translational research and data analytics offers the most promising path forward in reducing the global burden of sepsis.